POST GRADUATE RESEARCH IN THE HUMANITIES AT THE UNIVERSITY OF MALAYA - Awang Ngah, Zainab; Goi, Sook Sze (Malaysian Journal of Library and Information Science, 1997)
Studies research trends in the Humanities based on Master and Doctoral disserta-tions submitted to the University of Malaya library between 1984 and 1994. Disser-tation submission pattern increases 5 fold since the 1960s and the main contributors were post graduate students enrolled at the Faculty of Arts and Social Sciences and the Faculty of Education. Within the former faculty, the top three contributors were from the Departments of Malay studies, Islamic Studies and English studies. Researches were focussed on local studies and the highest research activity was indicated by researchers in Language and literature. Results from trend studies helped to identify the humanities research population, research trends and strength for effective resource allocation and formulation of plans to meet information needs amongst Humanities researchers.